Availability of literature on social entrepreneurship for sustainable wealth creation in Internet - Sarif, Suhaimi Mhd; Ismail, Yusof; Sarwar, Abdullah Al-Mamun (SatyaDham Foundation, 2012)
Social entrepreneurship has been the growing prominence for the last few decades. This paper examines relative availability of materials related to social entrepreneurship for sustainable wealth creation in order to develop hands-on, professional, ethical and what is promoted by the various organizations around the world. The main objective of this study was to examine the proportional frequency of social entrepreneurship and sustainable wealth creation by the organizations and other related concepts that are available in the Internet search engines. The study attempted to assess the availability of materials on social entrepreneurship for sustainable wealth creation on the Internet. The Internet was accessed on 03 April 2012 from 11:05 a.m. – 13:05 p.m.; 2.30 p.m. – 4:30 p.m. and 04 April 2012 from 9:30 a.m. – 11:00 a.m.; 11:30 p.m. – 1:00 p.m. Thus, 420 minutes were accessed to gather the hits information from various internet browsers. Basing on the hits received, various ratios were calculated which reflect statistically meaningful indices. The study is very significant for theoretical development of social entrepreneurship in sustainable wealth creation for companies in Malaysia as basing on the findings, this study have found that, the amount of materials on social entreprenureship and sustainable wealth creation are scarce. Thus, the result of this study provides some meaningful information on social entrepreneurship for sustainable wealth creation that can be developed further.